A Proposed Model for the Adoption of E-Learning Systems in Jordanian Universities - Ababneh, Hayel; AL-Gharaibeh, Shehadeh; Alserhan, Atalla; Al-Adamat, Abdullah; Al-jawazneh, Bahjat; Aleassa, Hasan (Journal of Posthumanism, 2025)
The purpose of this study is to propose a unified model by integrating the Unified Theory of Acceptance and Use of Technology (UTAUT), Task-Technology Fit model (TTF), Management Support, Computer Self-Efficacy, Perceived Trust, and Perceived Autonomy to investigate continuance intention to use e-learning systems within the educational institutions. The study used a deductive approach and quantitative methodology, in which causal hypotheses were tested to assess the connection between study variables. Data was collected by the use of a self-administered questionnaire, which was sent electronically to the targeted academics at both public and private universities in Jordan. Out of the returned surveys, 12 were invalid and 187 responses were usable for analysis. This study’s results verified that technology characteristics have the highest impact on the scholars’ perceived TTF, which indirectly led to their continuance intention to use e-learning system. In relation to the four constructs of UTAUT, it was found that performance expectancy and facilitating conditions are more responsible in the overall impact on the continuance intention. Amongst the exogenous variables, the results revealed that computer self-efficacy has the greatest impact. Essentially, the results strongly supported the research model to predict the continuance intention to use e-learning system by testing UTAUT, TTF, and other key conjectured variables. This paper contributes in providing a notable attention to the underlying factors that influence the continuance intention to adopt e-learning systems. Consequently, this paper integrates UTAUT and TTF and incorporates other factors into the unique proposed model to predict the continuance intention to adopt e-learning systems. On the practical side, this research also provides insights for developers and universities that can help them to improve their e-learning system to ensure sustained usage.